Feasibility and preliminary effects of an integrated hospital-to-home transitional care intervention for older adults with stroke and multimorbidity: A study protocol. (6th March 2019) - Markle-Reid, Maureen; Valaitis, Ruta; Bartholomew, Amy; Fisher, Kathryn; Fleck, Rebecca; Ploeg, Jenny; Salerno, Jennifer; Thabane, Lehana
Background: Stroke is a major life-altering event and the leading cause of death and disability in Canada. Most older adults who have suffered a stroke will return home and require ongoing rehabilitation in the community. Transitioning from hospital to home is reportedly very stressful and challenging, particularly if stroke survivors have multiple chronic conditions. New interventions are needed to improve the quality of transitions from hospital to home for this vulnerable population. Objectives: The primary objective of this study is to examine the feasibility of implementing a new 6-month transitional care intervention supported by a web-based app. The secondary objective is to explore its preliminary effects. Design: A single arm, pre/post, pragmatic feasibility study of 20–40 participants in Ontario, Canada. Participants will be community-dwelling older adults (≥55 years) with a confirmed stroke diagnosis, ≥2 co-morbid conditions, and referred to a hospital-based outpatient stroke rehabilitation centre. The 6-month transitional care intervention will be delivered by an interprofessional (IP) team and involve care coordination/system navigation, self-management education and support, home visits, telephone contacts, IP team meetings and a web-based app. Primary evaluation of the intervention will be based on feasibility outcomes (e.g. acceptability, fidelity). Preliminary intervention effects will be based on 6-month changes in health outcomes, patient experience, provider experience and cost. Conclusions: Information on the feasibility and preliminary effects of this newly-developed intervention will be used to optimize the design and methods for a future pragmatic trial to test the effectiveness and implementation of the intervention in other contexts and settings.